2006
DOI: 10.1001/archpedi.160.6.591
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Correlates of Unwanted Sex in Relationships of Middle and Late Adolescent Women

Abstract: Unwanted sex occurs often within the sexual relationships of teens. These unwanted sexual experiences result in risk for sexually transmitted infections and pregnancies. Sexual health counseling to reduce risk should focus on both the patient's and the partner's behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Comments such as "it just happened" and "I just gave in" indicated a lower sense of control over the timing of first intercourse, and conflicted with expectations of this transition being a "special" event. The context of these experiences, and more importantly, how teenagers interpreted the event from their own perspective adds more sophisticated understanding to this process over and above the extant quantitative literature on premature and unwanted sexual encounters [7,15,17,32].…”
Section: Discussionmentioning
confidence: 99%
“…Comments such as "it just happened" and "I just gave in" indicated a lower sense of control over the timing of first intercourse, and conflicted with expectations of this transition being a "special" event. The context of these experiences, and more importantly, how teenagers interpreted the event from their own perspective adds more sophisticated understanding to this process over and above the extant quantitative literature on premature and unwanted sexual encounters [7,15,17,32].…”
Section: Discussionmentioning
confidence: 99%
“…Other research has also found that unwanted sex is associated with lower rates of condom among adolescent girls. 38 One explanation, as suggested by the focus group findings, is that girls in an abusive relationship may have unprotected sex to avoid physical harm or because they have limited or no control over condom decision making. Yet, among girls who reported unwanted unprotected sex on the survey, a little less than a third of them reported no history of any of the 3 types of partner abuse that we assessed (physical, verbal, and threats).…”
Section: Unwanted Unprotected Sexmentioning
confidence: 99%
“…It may include psychological or verbal abuse and coercion in relation to sexual decision making, such as when the partner threatens to get angry or end the relationship, or it may actually include partner violence. It often occurs in a context in which the male partner has greater relationship power, meaning that his wishes hold more sway than hers (Blythe, Fortenberry, M'Hamed, Tu, & Orr, 2006). Intimate-partner violence against women occurs more often in economically disadvantaged communities, and minorities are overrepresented among those living in disadvantaged urban neighborhoods (Benson & Fox, 2004).…”
Section: Sexual Pressurementioning
confidence: 99%
“…Beyond young women feeling a lack of entitlement, another barrier to contraceptive use may involve partner negotiation when a girl and her male partner disagree about whether or not to have sex or to use a condom (Champion, Shain, & Piper, 2004;Tschann, Adler, Millstein, Gurey, & Ellen, 2002). In this context, unwelcome sexual pressure from male partners may confer added risk for girls to experience unwanted sexual encounters or unprotected sex (Blythe et al, 2006).…”
Section: Sexual Pressurementioning
confidence: 99%